Construcción con tecnología abierta de un sensor de turbidez de bajo costo (2016)
A novel device for measuring turbidity was designed and built.  The  device  was  prepared  using low cost  components  and  open  source  technology  such  as Arduinos, 3-D printers and open source software. The device consists of two main parts; firstly a LED which emits light and secondly a system that measures the light that passes through the  sample  holder. The amount of  light is quantified to obtain a value of the turbidity of the sample. A  detector  setup  with  two  light  receptors  aligned at  90º  with  respect  to  each  other  was  chosen  in  order to increase the sensitivity of the instrument. The device was calibrated and showed a sensitivity range between 50 and 650 Nephelometric Turbidity Unit (NTU). As part of the system validation test samples of the device were compared with those of a commercial HACH turbidity sensor and the disparity was just 3.3%. The device is intended  to  be  used  to  monitor  the  efficiency  of  removal of  suspended  particles  in  soils  as  well  as  treatment  of wastewater in rural regions of Ecuador.